Applications of the invariant subspace method on searching explicit solutions to certain special-type non-linear evolution equations - Qu, Gaizhu; Wang, Mengmeng; Shen, Shoufeng (Frontiers in Physics, 2023)
We extend the invariant subspace method (ISM) to a class of Hamilton-Jacobi equations (HJEs) and a family of third-order time-fractional dispersive PDEs with the Caputo fractional derivative in this letter. More precisely, the complete classification is presented for such HJEs that admit invariant subspaces governed by solutions of the second-order and third-order linear ordinary differential equations (ODEs). Meanwhile, some concrete equations are derived for the construction of new exact solutions u(x, t) = P ni=1 Ci(t)fi(x). Then a set of invariant subspaces of the considered third-order time-fractional nonlinear dispersive equations are obtained. Based on the Laplace transform method (LTM) and applying several properties of the well known Mitta-Leffer (ML) function, the different types of explicit solutions of a family of third-order time-fractional dispersive PDEs are finally derived.